Why the distribution of wealth matters: Industrial feudalism and social democracy - Szymborska, Hanna; Toporowski, Jan (PSL Quarterly Review, 2022)
This paper explains how growing inequality of wealth and asset inflation inhibits social mobility and the functioning of the labour market, whose efficiency is a key feature of macroeconomic theory and labour economics. However, because the composition of wealth differs between social classes, growing inequality of wealth tends to more rigid social stratification, preventing the social mobility that is held to be the great advantage of free market capitalism. The paper outlines a theory of wealth distribution and credit practices that maintain a more or less rigid system of social stratification, which we call industrial feudalism. The origin of this idea is found in the work of Polish economists and social critics in the first half of the last century. Industrial feudalism also restricts the functioning of the labour market. State welfare provision, which is supposed to overcome barriers to social mobility, is undermined when the propertied classes find that they can meet their welfare needs from cash flows generated by their wealth. In this way, industrial feudalism signals the end of the welfare state and social democracy.